Stable Orthorhombic CsPbBr3 Light Emitters: Encapsulation-Assisted In Situ Synthesis - Park, Jinwoo; Jang, Kyung Yeon; Lee, Song Hee; Kim, Dong-Hyeok; Cho, So-Hye; Lee, Tae-Woo (American Chemical Society, 2023)
Metal halide perovskite nanocrystals (PeNCs) are promisingcandidatesfor achieving Rec. 2020 with high color purity. However, the stabilityof PeNCs is inferior to that of conventional inorganic quantum dotemitters. Here, we developed a simple method using perhydropolysilazane(PSZ) to synthesize chemically stable CsPbBr3 PeNCs whilesimultaneously encapsulating them in a SiO2 matrix. Duringthe synthesis, PSZ converts to SiO2, encapsulates PeNCs,and forms stable Pb-O bonds with the orthorhombic CsPbBr3 crystal. Unlike cubic CsPbBr3 PeNCs synthesizedby conventional colloidal synthesis, this encapsulation-assisted insitu synthesis provided orthorhombic CsPbBr3 crystals withgood control over the crystallization and with an average crystalsize of 34.7 nm. Surprisingly, the resulting PeNC-PSZ compositesshowed a high photoluminescence quantum yield (PLQY) of 84.7% evenwithout the use of organic ligands surrounding the PeNCs. The orthorhombicCsPbBr(3) PeNCs in situ-synthesized using PSZ assistanceshowed higher chemical stability than cubic CsPbBr3 PeNCssynthesized by the conventional hot-injection method during storageunder ambient conditions and in water and under continuous externalenergy (100 & DEG;C hot plate, UV excitation). Contrary to the commonbelief regarding the low stability of ionic perovskites in water,orthorhombic CsPbBr3 PeNC in situ-synthesized using PSZassistance retained >60% of the initial PL intensity even afterlongstorage in water for >1100 h, which is more than 600 times longerthan those of emitters that use PeNCs synthesized using the conventionalhot-injection method.